Having a good credit rating without having borrowed before? A proposal for financial inclusion - Delgado Yábar, María Paz (2022)
Financial inclusion is both a process and a challenge, especially in countries like Peru, where many people are not part of the financial system. The author provides a business idea and a regulation proposal that could help in one of the aspects that affects the unbanked population, not having a credit record.The absence of a credit rating means that many people are rejected by the formal financial system, thus creating a vicious circle that leads to the development of a parallel informal financial system. The article proposes a novel way to help people build a credit history and thus be able to access more financial products at lower costs.